Leveraging technology to enhance global citizenship education: An online task based speaking skills module for technical and vocational education and training (TVET) learners - Mohd Khirulnizam, Musa (School of Educational Studies, USM, 2024)
Introduction: Global Citizenship Education (GCED) is increasingly recognized as a critical component in preparing individuals to navigate an interconnected world and address global challenges. As globalization intensifies, the ability to communicate effectively across cultures and understand global issues becomes paramount. This is particularly relevant for learners in Technical and Vocational Education and Training (TVET), who must be equipped not only with vocational skills but also with the competencies to engage in a globalized workforce. This paper presents an innovative approach to advancing GCED through the development and implementation of an online task-based speaking skills module tailored for TVET learners. Purpose of study: The primary aim of this study is to enhance the linguistic proficiency, intercultural competence, and awareness of global citizenship responsibilities among TVET learners through a technology-integrated speaking skills module. By focusing on authentic speaking practice opportunities that are relevant to learners' vocational fields, the study seeks to foster a deeper understanding of global issues and encourage learners to reflect on their roles as responsible global citizens. Methodology: The development of the online module involved several key stages: 1) Needs Analysis: conducting surveys and interviews with TVET educators and learners to identify specific speaking skills required in various vocational contexts, 2) Design and Development: creating multimedia materials and simulated workplace scenarios that provide realistic communication contexts. The module incorporates global themes to stimulate learners' interest in interconnected global issues, 3) Implementation: piloting the module with a group of TVET learners to gather feedback and make necessary adjustments and 4) Evaluation: assessing the effectiveness of the module through pre- and post-tests, learner feedback, and observations of learner engagement and performance. Discussions: The online task-based speaking skills module integrates several innovative features: a) Multimedia Materials: videos, audio recordings, and interactive content that provide diverse linguistic and cultural inputs; b) Simulated Workplace Scenarios: role-plays and situational tasks that mimic real-world vocational communication contexts, allowing learners to practice speaking skills in a safe and controlled environment; c) Collaborative Activities: group discussions, peer assessments, and collaborative projects that encourage active participation and the development of intercultural competence. By embedding global themes within these activities, the module not only improves linguistic skills but also raises awareness of global citizenship responsibilities. For example, learners engage in discussions about sustainable development, human rights, and ethical practices in their vocational fields. This approach helps learners connect their vocational training with broader global issues, fostering a sense of responsibility and engagement as global citizens. Conclusion: This study demonstrates that leveraging technology to enhance GCED through an online task-based speaking skills module can significantly benefit TVET learners. The module addresses barriers to access by providing flexible and inclusive learning opportunities, promoting linguistic proficiency and intercultural competence. By engaging with global themes, learners are better prepared to navigate the complexities of an interconnected world and contribute meaningfully to addressing global challenges. Future research could explore the long-term impacts of such initiatives and expand the approach to other educational contexts.